Evaluation of the effects of Chang’s attenuation correction technique on similar transverse views of cold and hot regions in Tc-99m SPECT: a phantom study - Sayed, Inayatullah Shah; Hassan, Aima Harfiza (Springer Berlin Heidelberg, 2011)
Approximate attenuation correction techniques are used to handle the effects of absorption of gamma photons in the patient’s body on image quality and quantification of radioactivity uptake. In this study, our aim is to evaluate the effects of Chang’s attenuation correction technique on cold and hot region images with various sizes and locations in the phantom having similar cross sectional views. Philip ADAC Forte dual head gamma camera is used. A novel phantom loaded with Tc-99m is scanned. Data acquisition parameters are chosen same as that in patient studies. Images are produced by filtered back projection technique. Chang’s attenuation correction is used with different linear attenuation coefficient (LAC) values. Cold and hot region images are analyzed in terms of regions detectability, contrast and standard deviation. Hot region images are also studied by relative count ratio. Results indicate that, cold region detectability is improved as compared to hot regions with all LAC values used here. No changes in the contrast of 22.4 mm diameter and decrease in 17.9 mm and 14.3 mm diameter cold region image are observed. Hot region image contrast of 13.4 mm diameter is enhanced, whereas, 22.4 mm and 17.9 mm diameter is equivocal with and without Chang’s technique.Relative count ratio of hot region images is improved. However, standard deviation in the count density of both types of regions is increased. Effects of Chang’s attenuation correction technique on cold and hot region images are different. Therefore, care must be taken in clinical studies.